A fivefold interpenetrating diamondoid three‐dimensional metal–organic framework constructed from benzene‐1, 4‐diacetic acid and flexible triazole derivatives: poly[[(μ2‐benzene‐1, 4‐diacetato‐κ2O:O)μ2‐1, 4‐bis[(1H‐1, 2, 4‐triazol‐1‐yl)methyl]benzene‐κ2N4:N4′zinc(II)] monohydrate]. Issue 1 (15th January 2014) - Shen, Hong
<x xml:space="preserve">Abstract</x> In the title mixed‐ligand metal–organic polymeric compound, [Zn(C10H8O4)(C12H14N6)]·H2On, the asymmetric unit contains a divalent ZnII cation lying on a twofold axis, one half of a fully deprotonated benzene‐1, 4‐diacetate (PBEA) ligand, one half of a 1, 4‐bis[(1H‐1, 2, 4‐triazol‐1‐yl)methyl]benzene (BTX) ligand and a water molecule, also lying on a twofold axis. Each ZnII centre is surrounded by two O‐donor atoms from monodentate carboxylate groups belonging to two different PBEA2− ligands and by two triazole N‐donor atoms from two different BTX ligands. Single‐crystal X‐ray diffraction analysis revealed that the compound has a fivefold interpenetrating diamondoid three‐dimensional metal–organic framework.